APPLICATION OF INFORMATION AND COMPUTER TECHNOLOGIES IN RUSSIAN LANGUAGE LESSONS IN PRIMARY GRADES - Yu.Yu. Melnychuk (Academy of Cognitive and Natural Sciences, 2010)
The article shows teaching potentialities of innovative technologies, it gives recom mendations on their use by a primary school teacher at the Russian language lessons. The article represents the scheme of applying information and computer technologies by a primary school teacher at the Russian language lessons.